SUPERIOR CERVICAL SYMPATHETIC GANGLION, SATELLITE GLIAL AND NERVE CELLS - Boljanović, Jelena (Medicinski podmladak, 2024)
The superior cervical sympathetic ganglion (SCSG), oval and fusiform in shape, is the highest and the most prominent of three cervical sympathetic chain ganglia vascularized by the ascending pharyngeal artery, branch of the external carotid artery. The SCSG provides sympathetic postganglionic innervation to the head and neck organs, and via the superior cervical cardiac branches the heart also. The SCSG contains two main types of cells, the satellite glial cells (SGCs) and ganglionic neurons (GNs). SGCs are located in the ganglia of peripheral nevous system (PNS), wrap around cell bodies of GNs in sensory, parasympathetic and sympathetic ganglia, and they have protective and supportive functions. SGCs are activated by inflammation and nerve injury, which enable them to interact with adjacent neurons, as well as they transmit signals to the preganglionic sympathetic synapses. These changes contribute to chronic pain by amplifying the neuronal activity. The important function of SGCs is in the formation of the blood-nervous tissue barrier of the peripheral nervous system, as well as in several pain syndromes commonly encountered in clinical practice. Sympathetic GNs are multipolar nerve cells micromorphologically. Preganglionic sympathetic axon form many axodendritic synapses with GNs dendrites, axosomatic synapses are less numerous. In the SCG the cell bodies of GNs contain neuropeptide Y (NPY), a potent vasoconstrictor, vasoactive intestinal polypeptide (VIP), vasodilator in CNS, but not the substance P (SP). The superior cervical sympathetic ganglion has a possible role in pain mechanisms and important role in controlling cardiovascular functions. Mast cells are normally present in the SCSG, could participate in the inflammatory process and may be involved in the development of pain.